1986
DOI: 10.2307/1242138
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Value of Time on Food Consumption Patterns in Developing Countries: Evidence from Sri Lanka

Abstract: This study shows that the opportunity cost of women's time can affect household food consumption patterns in developing countries. Demand equations for rice, bread, and the ratio of bread to total cereal consumption are estimated for urban Sri Lankan households. The demand specification, which is based on the “New Household Economics,” includes as explanatory variables the woman's estimated market wage and the household's “full income,” and alternatively “observed income.” Wages are estimated using the Heckman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 8 publications
1
33
0
4
Order By: Relevance
“…Differences have been observed in the way men and women spend their income shares. For example, Senauer et al (1986) found that in Sri Lanka an increase in women's earnings results in higher expenditures on bread than on rice. We analyzed expenditures on nine different expenditure groups by men and women using the income under their control.…”
Section: Control and Management Of Income By Men And Women And Expendmentioning
confidence: 99%
“…Differences have been observed in the way men and women spend their income shares. For example, Senauer et al (1986) found that in Sri Lanka an increase in women's earnings results in higher expenditures on bread than on rice. We analyzed expenditures on nine different expenditure groups by men and women using the income under their control.…”
Section: Control and Management Of Income By Men And Women And Expendmentioning
confidence: 99%
“…The coefficient of determination (R2) for the wage equation is .43 which is very high for a wage equation estimated with cross sectional data [Senauer, Sahn & Alderman (1986)]. …”
Section: Male Wage Rate Estimationmentioning
confidence: 99%
“…The use of microwave ovens, the choice of having fewer children, the substitution from time-intensive traditional food, such as rice, to time-saving food, such as commercially supplied bread [Senauer, Sahn & Alderman (1986)], are examples of this behavior.…”
mentioning
confidence: 99%
“…Muitos estudos vêm sendo feitos na tentativa de avaliar os efeitos de fatores socioeconômicos e demográficos nos padrões de consumo de alimentos para diversas regiões do mundo e vários autores já identificaram a importância de variáveis como a renda, raça, local de residência, tamanho e composição da família em mudanças nos padrões de consumo (PROCHASKA; SCHRIMPER, 1973;SENAUER, 1979;REDMAN, 1980;SENAUER;SAHN;ALDERMAN, 1986;McCRAKEN;BRANDT, 1987;PARK;CAPPS, 1997;SDRALI, 2005;SICHIERI;CASTRO;MOURA, 2005). Como exemplos de estudos nessa linha realizados para o Brasil, citam-se os trabalhos de Hoffmann (1995), que analisou o efeito da urbanização sobre o consumo de feijão e de Bertasso (2000), que fez uma análise sobre os efeitos de algumas variáveis socioeconômicas sobre o padrão de consumo de alimentos.…”
Section: Introductionunclassified